Impact of liver‐stiffness measurement on hepatocellular carcinoma development in chronic hepatitis C patients treated with direct‐acting antivirals: A systematic review and time‐to‐event meta‐analysis. Issue 3 (10th September 2020) - You, Myung‐Won; Kim, Kyung Won; Shim, Jae‐Jun; Pyo, Junhee
Abstract: Background and Aim: Patients with chronic hepatitis C (CHC) treated with direct‐acting antivirals (DAAs) are still at risk for developing hepatocellular carcinoma (HCC) even after achieving sustained virologic response (SVR). Liver‐stiffness measurement (LSM) on imaging has been investigated as a predictor of HCC occurrence. Objectives: To provide systematic summary of the predictive value of LSM in predicting HCC occurrence in HCV patients treated with DAA. Methods: A comprehensive literature search of the PubMed–MEDLINE and EMBASE databases was performed to identify studies that evaluated the predictive value of LSM in CHC patients treated with DAAs. Pooled hazard ratio (HR) comparing HCC occurrence between patients with positive and negative results on LSM was calculated for all studies and various subgroups. Subgroup analyses and meta‐regression were performed. Results: A review of 135 candidate articles identified eight eligible articles with a total of 3398patients for qualitative review and meta‐analysis. The pooled HR for HCC occurrence determined by LSM was 3.43 (95% confidence interval [CI], 1.63–7.19) with heterogeneity ( I 2 = 81.87%, P < 0.001), thus indicating that LSM might be helpful for predicting HCC occurrence. In subgroup analyses, pooled HRs were different according to the study design (2.29; [95% CI, 0.96–5.45] for retrospective studies; 4.61 [95% CI, 2.44–8.71] for prospective studies), study population (4.00 [95% CI, 2.00–7.99] for CHC; 2.64 [0.99–7.00] for CHC with liver cirrhosis) and LSM parameter (3.17 [95% CI, 1.35–7.41] for baseline LSM; 4.19 [95% CI, 1.89–9.29] for others). In multivariate meta‐regression, study design was the only influencing factor for pooled HR for HCC occurrence ( P < 0.05). Conclusions: Consistent evidence demonstrated the predictive value of LSM for HCC occurrence in CHC patients treated with DAA. The significant influencing factor for risk of HCC occurrence indicated by LSM was study design.